A computational corpus study of harmony in the music of Anton Webern - Ballance, J (2023)
This thesis sets out to apply digital analysis to the music of Anton Webern, with the aim of quantifying elements of his harmonic style, and tracing their change across his practice. It is a corpus study, taking Webern’s 31 works with Opus numbers as its subject, and uses music21 for the data collection. Analytical subjects include distributions of pitch classes, intervals, and pitch-class sets; techniques for assessing these include clustering, regression analysis, and the Discrete Fourier Transform. Along the way, the thesis interrogates commonly-held assumptions about Webern’s music for which there is often little empirical evidence, and provides a multi-level perspective on the corpus, from the wide angle of whole-movement macroharmonies to the close-up detail of individual pitch-class sets. Chronologically, the results suggest that the advent of dodecaphony in Webern’s music had a limited effect on the surface features of the music he presented; rather that the major shift in his practice happened in his mid-period Lieder. Contra Allen Forte, I downplay the importance of octatonicism in his harmonic language in favour of a quartal quality, but in the process I explore the differing features between the various harmonic levels of Webern’s music.